A new approach reveals syncytia within the visceral musculature of Drosophila melanogaster. - Klapper, R.; Heuser, S.; Strasser, T.; Janning, W. (Development, 2001)
In order to reveal syncytia within the visceral musculature of Drosophila melanogaster, we have combined the GAL4/UAS system with the single-cell transplantation technique. After transplantation of single cells from UAS-GFP donor embryos into ubiquitously GAL4-expressing recipients, the expression of the reporter gene was exclusively activated in syncytia containing both donor- and recipient-derived nuclei. In the first trial, we tested the system in the larval somatic musculature, which is already known to consist of syncytia. By this means we could show that most of the larval somatic muscles are generated by clonally non-related cells. Moreover, using this approach we were able to detect syncytia within the visceral musculature - a tissue that has previously been described as consisting of mononuclear cells. Both the longitudinal visceral musculature of the midgut and the circular musculature of the hindgut consist of syncytia and persist through metamorphosis. This novel application of the transplantation technique might be a powerful tool to trace syncytia in any organism using the GAL4/UAS system.